敗血症及び敗血症性ショックを予測する方法 (2024)
本発明の主題は、患者における敗血症、重症敗血症又は敗血症性ショックを予測するための方法であって、当該対象から得られた体液中のプロ－タキキニンＡ又は少なくとも５アミノ酸のその断片のレベルを決定することと、プロ－タキキニンＡ又は少なくとも５アミノ酸のその断片の決定されたレベルを敗血症又は敗血症性ショックと相関させることと、を含み、ある一定の閾値を超える上昇したレベルが、敗血症、重症敗血症又は敗血症性ショックを予測する、方法である。 Subject matter of the present invention is a method for predicting sepsis, severe sepsis or septic shock in a patient comprising determining the level of Pro-Tachykinin A or fragments thereof of at least 5 amino acids in a bodily fluid obtained from said subject, and correlating the determined level of Pro-Tachykinin A or fragments thereof of at least 5 amino acids with sepsis or septic shock, wherein an elevated level above a certain threshold is predictive of sepsis, severe sepsis or septic shock.